Bronchoscopy for Pulmonary Peripheral Lesions With Virtual Fluoroscopic Preprocedural Planning Combined With EBUS-GS: A Pilot Study. Issue 2 (April 2016) - Fukusumi, Munehisa; Ichinose, Yoshiaki; Arimoto, Yoshihito; Takeoka, Shinjiro; Homma, Chie; Matsuoka, Hiroyasu; Mouri, Atsuto; Hamamoto, Yoichiro; Matsumoto, Junichi; Kamimura, Mitsuhiro
Abstract : Background: Virtual fluoroscopic preprocedural planning (VFPP) is a figure in which the trace lines between the trachea and the target lesions are constructed along the connecting bronchus on Ray Summation image similar to fluoroscopy. The lines can be displayed at any angle with 3D imaging. This system was applied to bronchoscopy as a reference for forceps guidance under the fluoroscopy, as a new type of navigation. The objective of this study was to demonstrate the feasibility of VFPP. Methods: Patients with pulmonary peripheral lesions (PPLs) with long axis ⩽30 mm were recruited. Bronchoscopy with endobronchial ultrasonography with a guide sheath (EBUS-GS) was performed by using simultaneous display of VFPP. Results: For 27 patients with 27 lesions, endobronchial ultrasonography with a guide sheath with simultaneous display of VFPP was performed. The median lesion size was 20.2 mm (range, 10 to 30 mm). The median examination time was 24.5 minutes (range, 12 to 50 min). Diagnosis was made for 17 lesions of the total 27. Lung cancer was diagnosed in 12 lesions, nontuberculous mycobacterial disease in 1 lesion, lymphoid hyperplasia in 1 lesion, and inflammation in 3 lesions. In 10 lesions, no diagnosis was made. The diagnostic rate of the procedure was 63.0%. The sensitivity, specificity, negative predictive value, positive predictive value, and accuracy for malignant disease were 66.7%, 100%, 45.5%, 100%, and 73.9%, respectively. Conclusion: VFPP was easy to prepare and useful for selecting target bronchi. This study confirms feasibility of the VFPP as an adjunct to minimally invasive transbronchial biopsy of pulmonary peripheral lesions.